Conservation of concrete structures according to fib Model Code 2010. (December 2013) - Matthews, Stuart; Bigaj‐van Vliet, Agnieszka
Abstract Conservation of concrete structures forms an essential part of the fib Model Code for Concrete Structures 2010 (fib Model Code 2010). In particular, Chapter 9 of fib Model Code 2010 addresses issues concerning conservation strategies and tactics, conservation management, condition surveys, condition assessment, condition evaluation and decision‐making, making interventions and the recording of information for through‐life management. Chapter 9 incorporates the overall philosophy adopted in the development of fib Model Code 2010, which introduces a new integrated life cycle perspective into the design of concrete structures. Accordingly, Chapter 9 provides a response to concepts introduced earlier within fib Model Code 2010 relating to the service life design process, which requires the structure and its component parts to be allocated to a condition control category at the time of design. Different condition control categories are defined depending on factors such as the importance of the structure, its function, design service life, impact on third parties, environmental conditions, ease of maintenance and cost. The condition control levels and inspection regimes are defined in conjunction with these requirements. A through‐life management process, outlined in Chapter 9, provides feedback for service life design and allows the associated theoretical model employed to be updated, in turn facilitating the assessment of compliance with the original design objectives. An example of concrete structure conservation according to the fib Model Code 2010 concept is also presented.